Internalizing Quranic Values in the Development of Islamic Morals for Children with ADHD: An Inclusive Islamic Education Study - Azzahra, Hasna Safira; Mustofa, Triono Ali (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to conceptually analyze the internalization of Qur'anic values in the development of Islamic morals for children with Attention Deficit Hyperactivity Disorder (ADHD) in the framework of inclusive Islamic education. The research uses a qualitative approach through the library research method by examining scientific sources in the form of national and international books and articles published in 2021–2025 that are relevant to Qur'anic education, Islamic morals, inclusive Islamic education, and characteristics of ADHD children. Data were analyzed through a process of reduction, thematic categorization, and conceptual synthesis with a critical dialogue between literature findings. The results of the study show that the internalization of Qur'anic values in ADHD children faces obstacles in the form of limited attention, impulsivity, and weak self-regulation, so that cognitive-oriented and memorization learning approaches have not been effective in shaping religious behavior. Therefore, the internalization of Qur'anic values needs to be carried out through an inclusive, humanist, and process-oriented approach, such as gradual habituation, example, spiritual assistance, and concrete and contextual religious activities. This research has the value of originality in the development of an integrative conceptual framework that combines Qur'anic values, Islamic moral development, and the characteristics of ADHD child development in inclusive Islamic education, so that it can be a theoretical reference in the development of adaptive and sustainable moral development models.